ANALISIS FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN DARI GETAH KULIT BUAH PISANG GOROHO (Musa acuminate (L.)) - Kurniawan, Juliana Christie; Suryanto, Edi; Yudistira, Adithya (PHARMACON, 2013)
ABSTRACTThe objectives of this research was to analyze the phytochemical content and antioxidantactivity from goroho’s sap peel. Sample preparation was cut from the banana tier, then havebeen cut to the both base of goroho’s peel and the fresh sap collected into the petri dish. Theextraction method was maceration used 20, 40, 60 and 80% ethanol concentration.Phytochemical screening carried out by analysis of alkaloid, flavonoid, saponin, steroid,terpenoid and tannin. Determination of antioxidant activity performed by DPPH free radicalscavengers. The phytochemical analysis results was goroho’s sap peel contain flavonoid,saponin and tannin. Ethanol extract of goroho’s sap peel with 80% concentration 100 μg/mLhad the highest antioxidant activity. Results of this research concluded that phenolic extractsof goroho’s sap peel has the ability both as an antioxidant to DPPH free radicals.Keywords: Banana sap peel goroho, phytochemical, antioxidant activity